Pseudomonas aeruginosa RRALC3 Enhances the Biomass, Nutrient and Carbon Contents of Pongamia pinnata Seedlings in Degraded Forest Soil. - Parthasarathy Radhapriya; Andimuthu Ramachandran; Rangasamy Anandham; Sundararajan Mahalingam (PLoS ONE, 2015)
The study was aimed at assessing the effects of indigenous Plant Growth Promoting Bacterium (PGPB) on the legume Pongamia pinnata in the degraded soil of the Nanmangalam Reserve Forest (NRF) under nursery conditions. In total, 160 diazotrophs were isolated from three different nitrogen-free semi-solid media (LGI, Nfb, and JMV). Amongst these isolates, Pseudomonas aeruginosa RRALC3 exhibited the maximum ammonia production and hence was selected for further studies. RRALC3 was found to possess multiple plant growth promoting traits such as nitrogen accumulation (120.6ppm); it yielded a positive amplicon with nifH specific primers, tested positive for Indole Acetic Acid (IAA; 18.3μg/ml) and siderophore production, tested negative for HCN production and was observed to promote solubilization of phosphate, silicate and zinc in the plate assay. The 16S rDNA sequence of RRALC3 exhibited 99% sequence similarity to Pseudomonas aeruginosa JCM5962. Absence of virulence genes and non-hemolytic activity indicated that RRALC3 is unlikely to be a human pathogen. When the effects of RRALC3 on promotion of plant growth was tested in Pongamia pinnata, it was observed that in Pongamia seedlings treated with a combination of RRALC3 and chemical fertilizer, the dry matter increased by 30.75%. Nitrogen, phosphorus and potassium uptake increased by 34.1%, 27.08%, and 31.84%, respectively, when compared to control. Significant enhancement of total sugar, amino acids and organic acids content, by 23.4%, 29.39%, and 26.53% respectively, was seen in the root exudates of P. pinnata. The carbon content appreciated by 4-fold, when fertilized seedlings were treated with RRALC3. From the logistic equation, the rapid C accumulation time of Pongamia was computed as 43 days longer than the control when a combination of native PGPB and inorganic fertilizer was applied. The rapid accumulation time of N, P and K in Pongamia when treated with the same combination as above was 15, 40 and 33 days longer, respectively, as compared to the control.